Correlation Between Cognitive Function and Serum Levels of Brain-Derived Neutrophic Factor In Schizophrenia - Anissa, Mutiara; Akbar, Resti Rahmadika; Malik, Rifkind (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Schizophrenia is a chronic psychiatric disorder characterized by significant cognitive impairments, including deficits in attention, processing speed, and executive function. Brain-Derived Neurotrophic Factor (BDNF) is known to play a key role in neuroplasticity and cognitive processes; however, its relationship with cognitive function in schizophrenia remains unclear. Objective: this research aims to determine correlation between serum BDNF levels and cognitive function with Trail Making Test. Methods: A cross-sectional study was conducted on 50 schizophrenia patients. The population is schizophrenia patients at at Reksodiwiryo Padang Hospital Padang. The sampling method is a consecutive sampling. The statistical test used is Spearman’s correlation. Results: A significant proportion of participants demonstrated cognitive impairments (50% in Trail Making Test-A (TMT-A) and 60% in Trail Making Test-B), no statistically significant correlation was found between serum BDNF levels and TMT scores (TMT-A: r = -0.073, p = 0.612; TMT-B: r = -0.263, p = 0.065). Conclusion: This research concluded there was no statistically significant correlation between BDNF levels and TMT A and B. The findings suggest that serum BDNF may not directly correlate with cognitive impairments in schizophrenia, spesificly executive function and attention, as assessed by the TMT.